Role of Computed Tomography and Other Non-Invasive and Invasive Imaging Modalities in Cardiac Allograft Vasculopathy - Siddhant Passey; Jagriti Jha; Nirav Patel; Vincent Lipari; Saurabh Joshi; Raymond McKay; Joseph Radojevic; Joseph Ingrassia (Journal of Cardiovascular Development and Disease)
Cardiac allograft vasculopathy (CAV) is a leading cause of allograft dysfunction and failure. CAV prevention, early detection, and management are essential to increasing allograft survival. In this comprehensive review, we discuss various invasive and non-invasive modalities that are being utilized for CAV detection. Invasive coronary angiography provides a visualization of vascular anatomy but is limited in detecting the microvasculature and diffuse and early structural changes. The addition of intracoronary assessment techniques, including intravascular ultrasound, optical coherence tomography, and coronary flow reserve assessment, offer(s) superior sensitivity in identifying CAV. Non-invasive imaging modalities, such as cardiac magnetic resonance imaging, computed tomography angiography, and positron emission tomography, provide complementary insights into CAV with myocardial perfusion and allograft function while reducing procedural risks. Our aim is to guide clinicians in selecting appropriate imaging strategies tailored to individual recipients, to improve detection, monitoring, and outcomes in CAV.